2014
DOI: 10.1097/fbp.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent differences in the strength and persistence of psychostimulant-induced conditioned activity in rats

Abstract: The purpose of the present study was to determine the strength and persistence of cocaine-induced conditioned activity in young and adult rats. A one-trial protocol has proven useful for studying the ontogeny of psychostimulant-induced behavioral sensitization; therefore, a similar procedure was used to examine conditioned activity. On postnatal day (PD) 19 or PD 80, rats were injected with saline or cocaine in either a novel test chamber or the home cage. After various drug abstinence intervals (1–21 days), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Regardless of habituation day, adult rats exhibited more locomotor activity than preweanling rats, with adolescent rats being intermediate between and significantly different from the younger and older age groups. The finding that preweanling rats locomoted less than adults has been observed before in both habituated and nonhabituated animals (McDougall et al 2007, 2014a; but see Campbell et al 1969). Less clear is the relationship between adolescents and adults, because adult rats and mice were found to exhibit more (Adriani and Laviola 2000; Koek et al 2012; McDougall et al 2014a), less (Lanier and Isaacson 1977; Spear and Brake 1983), or similar levels of basal locomotor activity when compared to adolescent rodents (White and Holtzman 2005; Zombeck et al 2010).…”
Section: Discussionsupporting
confidence: 69%
“…Regardless of habituation day, adult rats exhibited more locomotor activity than preweanling rats, with adolescent rats being intermediate between and significantly different from the younger and older age groups. The finding that preweanling rats locomoted less than adults has been observed before in both habituated and nonhabituated animals (McDougall et al 2007, 2014a; but see Campbell et al 1969). Less clear is the relationship between adolescents and adults, because adult rats and mice were found to exhibit more (Adriani and Laviola 2000; Koek et al 2012; McDougall et al 2014a), less (Lanier and Isaacson 1977; Spear and Brake 1983), or similar levels of basal locomotor activity when compared to adolescent rodents (White and Holtzman 2005; Zombeck et al 2010).…”
Section: Discussionsupporting
confidence: 69%
“…In the animals treated with IN-DA before VEH, these behaviors did not decrease in comparison with VEH, suggesting DA conditioned behavioral effects as a likely cause, i.e., the normal behavioral response to VEH could have been masked or modified as a result of Pavlovian conditioning of the unconditioned response to the preceding IN-DA. Such an interpretation is consistent with a large literature describing Pavlovian conditioned behavioral responses and sensitization to psychoactive drugs, such as cocaine and amphetamine (Carey et al, 2014 ), and particularly with the results of McDougall et al ( 2014 ), who found one-trial induced cocaine conditioned activity, which persisted for at least 21 days in rats. This interpretation is also consistent with the evidence above for a Pavlovian conditioned DA response to VEH when VEH was preceded by IN-DA.…”
Section: Discussionsupporting
confidence: 91%
“…Signaling by extracellular signal-regulated kinase (ERK) has also been shown to play a role in Pavlovian psychostimulant conditioning (Lu et al, 2006 ). One-trial induced Pavlovian conditioned behavioral response to cocaine has been shown to persist for at least 21 days in rats (McDougall et al, 2014 ). Such results lend credence to an interpretation of our results in terms of Pavlovian drug conditioning to IN-DA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the inability of ketamine to induce conditioned activity is unique to early ontogeny. Indeed, preweanling rats (PD 10–PD 21) do not show cocaine-induced conditioned activity even after 10 daily environment-drug pairings (Zavala et al 2000; see also Wood et al 1998; McDougall et al 1999; 2014). The reason for this age-dependent effect is unknown, but Spear and colleagues have shown that young rats perceive and process CSs differently than adults (for reviews, see Spear et al 1988; Spear and McKenzie 1994).…”
Section: Discussionmentioning
confidence: 99%